Since They Can’t Turn Back Time: How Companies Can Ensure a Well-Received Apology - Bitter,Friederike Carlotta; Mykoo,Sian Anya-Fay; Ziegler,Alina (LBMG Strategic Brand Management - Masters Paper Series, 2025)
Abstract Purpose: The purpose of this paper is to investigate the key factors that contribute to the success of corporate apologies issued in response to a crisis. Methodology: This paper uses a qualitative research method. The primary data was collected in the form of case studies of 30 apologies across three decades and multiple industries. These cases were analyzed using relevant theories found in the literature. The secondary data consists of literature within the field of study. Findings: Through the research it was found that brand relationship is a key aspect in issuing an effective and well-received apology as it should align with the content. With this finding we adapted Kador’s 5R framework and included brand relationship as an overarching dimension. This framework provides concrete guidelines for companies. Research Limitation: As every crisis is unique, individual contextual analysis remains essential when issuing an apology. Furthermore, most cases in the analysis are based on western countries. Cultural differences may affect how apologies are issued and perceived. More research in other continents should be conducted to create a more balanced perspective and verify our framework and resulting guidelines. Practical Contributions: Companies should issue apologies quickly, ensure that the decision of delivery method and spokesperson fits the severity of the crisis and most importantly the content aligns with the brand relationship and includes Kador’s 5Rs. We suggest that crisis and brand managers work hand in hand. Key Words: Corporate Apology, Trust, Image, Reputation, Recognition, Responsibility, Remorse, Restitution, Repetition Paper Type: Research Paper
Keywords: Corporate Apology; Trust; Image; Reputation; Recognition; Responsibility; Remorse; Restitution; Repetition